Water-based medical packaging adhesive and preparation method thereof
By using acrylic emulsion, polyester emulsion, polymer phenol and antioxidant and other raw materials, prepare a water -based medical packaging adhesive with good aging resistance, solving the problem of existing adhesives after accelerating the yellow change. , Achieve more stable performance.
Patent Information
- Application Number
- CN202411351767.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
AI Technical Summary
Existing water-based medical packaging adhesives have insufficient aging resistance after accelerated aging and are prone to yellowing.
Adopt raw materials such as acrylic emulsion, polyester emulsion, polymer phenol and antioxidant, and prepare a water -based medical packaging adhesive through a specific stirring speed and time.
Improve the aging performance of adhesives, prevent the phenomenon of yellow change when accelerating aging, while maintaining the peeling strength and sealing.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical packaging materials, and in particular to a water-based medical packaging adhesive and a preparation method thereof. Background Art
[0002] Water-based adhesives are environmentally friendly adhesives made from natural or synthetic polymers and water as a solvent or dispersant, replacing toxic organic solvents that pollute the environment.
[0003] In order to facilitate ethylene oxide sterilization, the packaging of medical devices usually has at least one side of medical paper. The specific processing process of the packaging box or packaging bag is to spray the water-based adhesive on the medical paper, and then put it into the bag making machine / online packaging machine for hot pressing and bonding with the coated paper / PVC / PS coil to form a packaging bag or packaging box. The peel strength between the medical paper and the coated paper / PVC / PS coil after bonding is 4±1N / 15mm. When the medical paper is torn apart during use, the peeling between the medical paper and the coated paper / PVC / PS coil is gentle. After separation, the adhesive layer is transferred to the coated paper / PVC / PS coil, and the paper fibers of the medical paper will not be extracted, but paper scraps will fall off. A solution prepared with 0.15% Tween, 0.15% Amaranth, 5% alcohol, and 100 ml H2O is placed in a heat-sealed paper bag / paper box and does not leak at room temperature for 20 seconds. It is easy to use, has moderate strength, and good sealing properties.
[0004] Most of the water-based medical packaging adhesives on the market are made of water-based polyurethane, polyethylene wax emulsion, deionized water, ethylene-vinyl acetate copolymer emulsion and other raw materials. After accelerated aging at 58°C for 150 days, the packaging paper bags or paper boxes made of water-based medical packaging adhesives currently sold on the market will turn yellow where the adhesive is sprayed, and the aging resistance is insufficient. Summary of the invention
[0005] The purpose of the present invention is to provide a water-based medical packaging adhesive with good aging resistance and no yellowing during accelerated aging; another purpose of the present invention is to provide a preparation method of the water-based medical packaging adhesive with good aging resistance and no yellowing during accelerated aging.
[0006] The present invention discloses a water-based medical packaging adhesive, wherein the raw materials include, by weight:
[0007] Acrylic emulsion 48-52 parts;
[0008] 0.1-0.3 parts of polymerized hindered phenol;
[0009] 48-52 parts of polyester emulsion;
[0010] Antioxidant 0.1-0.3 parts.
[0011] Acrylic emulsion has good adhesion, weather resistance and film-forming properties; polyester emulsion has the advantages of high strength, good film-forming properties and high toughness; polymerized hindered phenols and antioxidants mainly have antioxidant effects, and they have high stability after addition and have a protective effect on water-based medical packaging adhesives.
[0012] Furthermore, the acrylic emulsion is CX-104 acrylic emulsion.
[0013] Furthermore, the polymerized hindered phenol is polymerized hindered phenol KY616-3.
[0014] Furthermore, the polyester emulsion is CX-107 polyester emulsion.
[0015] Furthermore, the antioxidant is LX-826 thioester antioxidant.
[0016] Further, in parts by weight, the raw materials include:
[0017] Acrylic emulsion 50 parts;
[0018] 0.2 parts of polymerized hindered phenol;
[0019] 50 parts of polyester emulsion;
[0020] 0.2 parts of antioxidant.
[0021] The present invention also provides a method for preparing a water-based medical packaging adhesive, which comprises the following steps according to the raw material ratio of the water-based medical packaging adhesive as described above:
[0022] S1: Take acrylic emulsion and stir;
[0023] S2: adding polymerized hindered phenol to the acrylic emulsion of step S1, and stirring to mix evenly;
[0024] S3: adding the polyester emulsion to the mixture obtained in step S2, and stirring to mix evenly;
[0025] S4: adding an antioxidant to the mixture obtained in step S3, stirring and mixing the mixture evenly to obtain a water-based medical packaging adhesive.
[0026] Furthermore, in steps S1-S4, the stirring speed remains unchanged, the stirring speed is 9-11 Hz, and the preparation process takes 50-70 minutes.
[0027] Controlling the stirring speed at 9-11Hz can make the various ingredients fully mixed and ensure the adhesive strength of the glue reaches the best state. For example, acrylic emulsion, polyester emulsion and other ingredients can better blend with each other, so that the glue forms a stronger bond when bonding different materials; stirring too fast will introduce more air, forming bubbles, which will reduce the bonding strength.
[0028] Controlling the stirring speed at 9-11Hz will help to evenly disperse the components of the glue and improve the stability of the glue. Improper stirring speed may cause the components to separate or precipitate, making the glue unstable during use.
[0029] The invention provides a water-based medical packaging adhesive, which adopts acrylic emulsion to enhance the strength of paper so that the paper is not easily torn; the polyester emulsion has unique chemical properties, which can interact with the acrylic emulsion to a certain extent on the one hand, and react with the film material during heat sealing to bond the film material on the other hand, so that the acrylic emulsion and the film material (coated paper / PVC / PS) can be connected, and the water-based medical packaging adhesive can be transferred to the film material after the packaging bag / box is torn; the polymerized hindered phenol and the antioxidant can increase the aging resistance of the acrylic emulsion and the polyester emulsion; after the adhesive is prepared, the adhesive will not decompose during accelerated aging and will not yellow. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the accelerated aging color difference results of the embodiments and comparative examples in the present invention. DETAILED DESCRIPTION
[0031] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] Example 1
[0033] Preparation of water-based medical packaging adhesive:
[0034] Step 1, add 50 kg of CX-104 acrylic emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0035] Step 2, adding 0.1 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0036] Step 3, add 50 kg of CX-107 polyester emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0037] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0038] Example 2
[0039] Preparation of water-based medical packaging adhesive:
[0040] Step 1, add 50 kg of CX-104 acrylic emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0041] Step 2, adding 0.15 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0042] Step 3, add 50 kg of CX-107 polyester emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0043] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0044] Example 3
[0045] Preparation of water-based medical packaging adhesive:
[0046] Step 1, add 50 kg of CX-104 acrylic emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0047] Step 2, adding 0.20 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0048] Step 3, add 50 kg of CX-107 polyester emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0049] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0050] Example 4
[0051] Preparation of water-based medical packaging adhesive:
[0052] Step 1, add 50 kg of CX-104 acrylic emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0053] Step 2, adding 0.25 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0054] Step 3, add 50 kg of CX-107 polyester emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0055] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0056] Example 5
[0057] Preparation of water-based medical packaging adhesive:
[0058] Step 1, add 50 kg of CX-104 acrylic emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0059] Step 2, adding 0.3 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0060] Step 3, add 50 kg of CX-107 polyester emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0061] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0062] Comparative Example 1
[0063] Directly purchase commercially available medical packaging boxes (the manufacturer is Bimax, model is PS55).
[0064] Comparative Example 2
[0065] Preparation of water-based medical packaging adhesive:
[0066] Step 1, add 50 kg of TL-531 polyethylene wax emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0067] Step 2, adding 0.20 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0068] Step 3, add 50 kg of CX-107 polyester emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0069] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0070] Comparative Example 3
[0071] Preparation of water-based medical packaging adhesive:
[0072] Step 1, add 50 kg of CX-104 acrylic emulsion into a mixing barrel and perform physical stirring at a uniform speed;
[0073] Step 2, adding 0.3 kg of polymeric hindered phenol KY616-3 material to step 1 and stirring thoroughly;
[0074] Step 3, add 50 kg of CW40-905 ethylene-vinyl acetate copolymer emulsion into the mixing barrel and perform physical stirring at a uniform speed;
[0075] Step 4, adding 0.2 kg of antioxidant LX-826 material in step 3 and stirring thoroughly to obtain a water-based medical packaging adhesive.
[0076] Performance Testing:
[0077] The medical packaging adhesives prepared in Examples 1-5 and Comparative Examples 1-3 are coated on medical paper by roller coating, and then sealed together with the PVC film material through packaging equipment under the effects of molding, temperature, speed and pressure to form a packaging box.
[0078] 1000 packaging boxes processed from Examples 1-5 and Comparative Examples 1-3 were taken for accelerated aging test. The test was conducted with reference to ASTM F1980-2016 Standard Guide for Accelerated Aging of Sterile Medical Device Packages. The conditions of this accelerated aging test were: placing the sterile box in an aging box at 58°C (assuming that the average real-time temperature of the product during the entire shelf life is 22°C) for 150 days. According to the method in ASTM1980, AAT = 5 years, AAF = 12.13, and so on. The 150-day sample is equivalent to the 5-year sample at room temperature.
[0079] Reference standard for peel force: ISO11607-1:2016: Packaging of terminally sterilized medical devices Part 1: Requirements for materials, sterile barrier systems and packaging systems, testing the peel force of the packaging box.
[0080] All packaging boxes are tested for leakage and hand-tear chips.
[0081] The test results are as follows:
[0082] The average peeling force obtained in the test of Example 1 was 3.75N / 15mm, and there was no leakage of paper scraps;
[0083] The average peeling force after 30 days of accelerated aging is 3.27N / 15mm, with no leakage or paper scraps falling off;
[0084] The average peeling force after 60 days of accelerated aging is 3.53N / 15mm, with no leakage or paper scraps falling off;
[0085] The average peeling force after 90 days of accelerated aging is 4.52N / 15mm, with no leakage or paper scraps falling off;
[0086] The average peeling force after 120 days of accelerated aging is 4.22N / 15mm, with no leakage or paper scraps falling off;
[0087] The average peeling force after 150 days of accelerated aging is 4.75N / 15mm, with no leakage or paper scraps falling off.
[0088] The peeling force obtained in the test of Example 2 is 4.05N / 15mm, and there is no leakage or paper scraps falling;
[0089] The average peeling force after 30 days of accelerated aging is 3.57N / 15mm, with no leakage or paper scraps falling off;
[0090] The average peeling force after 60 days of accelerated aging is 3.46N / 15mm, with no leakage or paper scraps falling off;
[0091] The average peeling force after 90 days of accelerated aging is 4.51N / 15mm, with no leakage or paper scraps falling off;
[0092] The average peeling force after 120 days of accelerated aging is 3.79N / 15mm, with no leakage or paper scraps falling off;
[0093] The average peeling force after 150 days of accelerated aging is 4.15N / 15mm, with no leakage or paper scraps falling off.
[0094] The average peeling force obtained in the test of Example 3 was 3.89N / 15mm, and there was no leakage or paper scraps falling off;
[0095] The average peeling force after 30 days of accelerated aging is 3.71N / 15mm, with no leakage or paper scraps falling off;
[0096] The average peeling force after 60 days of accelerated aging is 4.03N / 15mm, with no leakage or paper scraps falling off;
[0097] The average peeling force after 90 days of accelerated aging is 4.38N / 15mm, with no leakage or paper scraps falling off;
[0098] The average peeling force after 120 days of accelerated aging is 4.12N / 15mm, with no leakage or paper scraps falling off;
[0099] The average peeling force after 150 days of accelerated aging is 4.27N / 15mm, with no leakage or paper scraps falling off.
[0100] The average peeling force obtained in the test of Example 4 was 3.71 N / 15 mm, with no leakage or paper scraps falling off;
[0101] The average peeling force after 30 days of accelerated aging is 4.19N / 15mm, with no leakage or paper scraps falling off;
[0102] The average peeling force after 60 days of accelerated aging is 3.36N / 15mm, with no leakage or paper scraps falling off;
[0103] The average peeling force after 90 days of accelerated aging is 4.49N / 15mm, with no leakage or paper scraps falling off;
[0104] The average peeling force after 120 days of accelerated aging is 3.92N / 15mm, with no leakage or paper scraps falling off;
[0105] The average peeling force after 150 days of accelerated aging is 4.36N / 15mm, with no leakage or paper scraps falling off.
[0106] The average peeling force obtained in the test of Example 5 was 4.22N / 15mm, with no leakage or paper scraps falling off;
[0107] The average peeling force after 30 days of accelerated aging is 3.65N / 15mm, with no leakage or paper scraps falling off;
[0108] The average peeling force after 60 days of accelerated aging is 4.62N / 15mm, with no leakage or paper scraps falling off;
[0109] The average peeling force after 90 days of accelerated aging is 3.88N / 15mm, with no leakage or paper scraps falling off;
[0110] The average peeling force after 120 days of accelerated aging is 3.91N / 15mm, with no leakage or paper scraps falling off;
[0111] The average peeling force after 150 days of accelerated aging is 4.46N / 15mm, with no leakage or paper scraps falling off;
[0112] The average peeling force obtained in the test of Comparative Example 1 was 4.69N / 15mm, with no leakage or paper scraps falling off;
[0113] The average peeling force after 30 days of accelerated aging is 4.38N / 15mm, with no leakage or paper scraps falling off;
[0114] The average peeling force after 60 days of accelerated aging is 5.62N / 15mm, with no leakage or paper scraps falling off;
[0115] The average peeling force after 90 days of accelerated aging is 4.91N / 15mm, with no leakage or paper scraps falling off;
[0116] The average peeling force after 120 days of accelerated aging is 4.21N / 15mm, with no leakage or paper scraps falling off;
[0117] The average peeling force after 150 days of accelerated aging is 4.82N / 15mm, with no leakage or paper scraps falling off.
[0118] The average peeling force obtained in the test of Comparative Example 2 was 3.46N / 15mm, with leakage but no paper scraps falling off;
[0119] The average peeling force after 30 days of accelerated aging is 3.29N / 15mm, with no leakage or paper scraps falling off;
[0120] The average peeling force after 60 days of accelerated aging is 3.61N / 15mm, with no paper scraps falling off and leakage;
[0121] The average peeling force after 90 days of accelerated aging is 4.08N / 15mm, with leakage but no paper scraps falling off;
[0122] The average peeling force after 120 days of accelerated aging is 3.27N / 15mm, with leakage but no paper scraps falling off;
[0123] The average peeling force after 150 days of accelerated aging is 3.42N / 15mm, with leakage but no paper scraps falling off;
[0124] The average peeling force obtained in the test of Comparative Example 3 was 5.23N / 15mm, with paper scraps falling off but no leakage;
[0125] The average peeling force after 30 days of accelerated aging is 4.37N / 15mm, with no leakage and some paper scraps falling off;
[0126] The average peeling force after 60 days of accelerated aging is 4.96N / 15mm, with no leakage and some paper scraps falling off;
[0127] The average peeling force after 90 days of accelerated aging is 5.21N / 15mm, with no leakage and some paper scraps falling off;
[0128] The average peeling force after 120 days of accelerated aging is 5.39N / 15mm, with paper scraps falling off but no leakage;
[0129] The average peeling force after 150 days of accelerated aging is 5.54N / 15mm, with some paper scraps falling off but no leakage.
[0130] Observe the appearance of all packaging boxes, record the number of packaging boxes that have color changes, and make a color difference test pass rate result chart based on the obtained data, such as Figure 1 shown.
[0131] according to Figure 1 As shown, after adding polymer hindered phenol and antioxidant, the aging performance of the packaging box is greatly improved. When the addition amount of polymer hindered phenol KY616-3 is greater than or equal to 0.2 kg, no yellowing phenomenon occurs during 150 days of accelerated aging.
[0132] The peel strength test results of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.
[0133] Table 1 Test results of average peel force in accelerated aging test
[0134] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 30 days 3.27 3.57 3.71 4.36 3.65 4.38 3.29 4.37 60 days 3.53 3.46 4.03 3.36 4.62 5.62 3.61 4.96 90 days 4.52 4.51 4.38 4.49 3.88 4.91 4.08 5.21 120 days 4.22 3.79 4.12 3.92 3.91 4.21 3.27 5.39 150 days 4.75 4.15 4.27 4.36 4.46 4.82 3.42 5.54
[0135] like Figure 1 As shown in Table 1, compared with Comparative Example 1, the anti-aging and discoloration performance of Examples 1-5 is significantly enhanced, and when the amount of stabilizer KY616-3 added is 0.2 kg, the aging is most stable from 30 days to 150 days, and no paper scraps fall off. After using acrylic emulsion and polyester emulsion, after the packaging box is peeled off, there will be no phenomenon of paper fibers being pulled out and paper scraps falling off.
[0136] like Figure 1As shown in Table 1, the yellowing value and average peeling force of Example 3 in the aging test are more stable. The preferred formula includes, by weight: 50 parts of acrylic emulsion, 0.2 parts of stabilizer, 50 parts of polyester emulsion, and 0.2 parts of antioxidant.
[0137] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A water-based medical packaging adhesive, characterized in that: In parts by weight, the raw materials include: Acrylic emulsion 48-52 parts; 0.1-0.3 parts of polymerized hindered phenol; 48-52 parts of polyester emulsion; Antioxidant 0.1-0.3 parts.
2. The aqueous medical packaging adhesive according to claim 1, characterized in that: The acrylic emulsion is CX-104 acrylic emulsion.
3. The aqueous medical packaging adhesive according to claim 1, characterized in that: The polymer hindered phenol is polymer hindered phenol KY616-3.
4. The aqueous medical packaging adhesive according to claim 1, characterized in that: The polyester emulsion is CX-107 polyester emulsion.
5. The aqueous medical packaging adhesive according to claim 1, characterized in that: The antioxidant is LX-826 thioester antioxidant.
6. The aqueous medical packaging adhesive according to claim 1, characterized in that: In parts by weight, the raw materials include: Acrylic emulsion 50 parts; 0.2 parts of polymerized hindered phenol; 50 parts of polyester emulsion; 0.2 parts of antioxidant.
7. A method for preparing a water-based medical packaging adhesive, characterized in that: According to the raw material ratio of the water-based medical packaging adhesive as described in any one of claims 1 to 6, the following steps are included: S1: Take acrylic emulsion and stir; S2: adding polymerized hindered phenol to the acrylic emulsion of step S1, and stirring to mix evenly; S3: adding the polyester emulsion to the mixture obtained in step S2, and stirring to mix evenly; S4: adding an antioxidant to the mixture obtained in step S3, stirring and mixing the mixture evenly to obtain a water-based medical packaging adhesive.
8. The method for preparing a water-based medical packaging adhesive according to claim 7, characterized in that: In steps S1-S4, the stirring speed is kept constant, the stirring speed is 9-11 Hz, and the preparation process is 50-70 min.